The Characteristics of Treated Pulmonary Arterial Hypertension Patients in Ontario - Haris M. Vaid; Ximena Camacho; John T. Granton; Muhammad M. Mamdani; Zhan Yao; Samantha Singh; David N. Juurlink; Tara Gomes (Canadian Respiratory Journal)
Background. There are no Canadian prevalence studies on pulmonary arterial hypertension (PAH) to date. We described the characteristics of treated PAH patients and the healthcare utilization and costs associated with PAH in a population of public drug plan beneficiaries in Ontario, Canada. Methods. A retrospective cross-sectional analysis was conducted between April 2010 and March 2011 to identify treated PAH patients using population-based health administrative databases. We investigated demographic and clinical characteristics of treated PAH patients and conducted a cohort study to determine treatment patterns, healthcare utilization, and associated costs, over a one-year follow-up period (March 2012). Results. We identified 326 treated PAH cases in Ontario’s publicly funded drug plan. Overall mean age was 59.4 years (±20.3 years) and over 77% of cases were women (n=251). Combination therapy was used to treat 22.9% (n=69) of cases, costing an average of $4,569 (SD $1,544) per month. Median monthly healthcare costs were $264 (IQR $96–$747) for those who survived and $2,021 (IQR $993–$6,399) for those who died over a one-year period, respectively (p<0.01). Conclusions. PAH care in Ontario is complex and has high healthcare costs. This data may help guide towards improved patient management.